Targeting the Gut Mucosal Immune System Using Nanomaterials - Jacob McCright (MDPI AG, 2021)
The gastrointestinal (GI) tract is one the biggest mucosal surface in the body and one of the primary targets for the delivery of therapeutics, including immunotherapies. GI diseases, including, e.g., inflammatory bowel disease and intestinal infections such as cholera, pose a significant public health burden and are on the rise. Many of these diseases involve inflammatory processes that can be targeted by immune modulatory therapeutics. However, nonspecific targeting of inflammation systemically can lead to significant side effects. This can be avoided by locally targeting therapeutics to the GI tract and its mucosal immune system. In this review, we discuss nanomaterial-based strategies targeting the GI mucosal immune system, including gut-associated lymphoid tissues, tissue resident immune cells, as well as GI lymph nodes, to modulate GI inflammation and disease outcomes, as well as take advantage of some of the primary mechanisms of GI immunity such as oral tolerance.